PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. RODANIAGA KOKOH NUSANTARA KABUPATEN TANGERANG - Eka Suryani; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of work discipline and the physical work environment on employee performance at PT Rodaniaga Kokoh Nusantara, Tangerang Regency. The method used is descriptive quantitative with associative properties. The sampling technique used saturated samples and a sample of 60 respondents was obtained. The data analysis method in this research uses the SPSS IBM application version 29. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that work discipline has a significant effect on employee performance with a coefficient of determination value of 65.4% and the hypothesis test obtained t count > t table or (10.314 > 2.002). The physical work environment has a significant effect on employee performance with a coefficient of determination value of 65.4% and the hypothesis test obtained t count > t table or (2.068 > 2.002). Work discipline and the physical work environment simultaneously have a significant effect on employee performance with the regression equation Y = 7.934 + 0.728X1 + 0.065X2. The coefficient of determination value is 65.4% while the remaining 34.6% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (53.758 > 3.16).